2008
DOI: 10.1590/s0102-09352008000500017
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros de fermentação de silagens de cana-de-açúcar submetidas a diferentes tratamentos

Abstract: Parâmetros de fermentação de silagens de cana-de-açúcar submetidas a diferentes tratamentos RESUMOOs valores de materia seca (MS), pH, teores de N-NH 3 /NT, ácidos orgânicos e etanol, de silagens de cana-de-açúcar foram determinados, em delineamento experimental em blocos ao acaso. Os tratamentos aplicados à silagens foram: sem aditivo, testemunha (T); 0,5% de uréia (U); 0,5% de zeólita (Z); 0,5% de uréia mais 0,5% de zeólita (U+Z); inoculante bacteriano/enzimático Bio Max® cana (IBB) e inoculante bacteriano S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
3
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 4 publications
1
6
3
10
Order By: Relevance
“…These results differ from those found by Castro Neto et al (2008), who evaluated the inoculation of sugarcane silage with Lactobacillus plantarum (Biomax 5) and observed no effects on DM, NH 3 /total N and soluble carbohydrates content, as well as no effects on lactic, acetic and butyric acids and ethanol. According to the authors, the reason for this result may have been the reduced or similar growth rate of the inoculated microorganisms in comparison with that of the native silage microbial population.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…These results differ from those found by Castro Neto et al (2008), who evaluated the inoculation of sugarcane silage with Lactobacillus plantarum (Biomax 5) and observed no effects on DM, NH 3 /total N and soluble carbohydrates content, as well as no effects on lactic, acetic and butyric acids and ethanol. According to the authors, the reason for this result may have been the reduced or similar growth rate of the inoculated microorganisms in comparison with that of the native silage microbial population.…”
Section: Resultscontrasting
confidence: 99%
“…By decreasing the ethanol production, lower losses of volatile compounds will occur during the oven drying process of dry matter content determination, thereby increasing the silage DM content. Castro Neto et al (2008) evaluated the inoculation of sugarcane silages with Lactobacillus plantarum (Biomax 5) and observed that there were no effects on DM and soluble carbohydrates contents, which partially concurs with the present results. In the study of Schneider et al (1995), the inoculation of wet brewer grains silages with Lactobacillus plantarum and Streptococcus faecium did not have effects on DM, CP, NDF or ADF contents, but decreased soluble carbohydrates concentrations, which also partially agrees with the present findings.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Plant cell urease converts urea applied to ensiled forages into ammonia and the additive applied at the dose of 5.0 g/kg FF resulted in reductions in yeast counts, lower ethanol content and DM losses and higher digestibility in sugarcane silages of previous experiments CAstro Neto et al, 2008;2008). Higher doses of urea may result in inadequate pH and higher DM losses in the silage (siqueirA et al, 2010).…”
Section: Trialmentioning
confidence: 99%
“…Valor Neto et al (2008), que também observaram aumentos nos teores de N-NH 3 e PB quando foi utilizada uréia como aditivo na ensilagem de cana-de-açúcar.…”
Section: Tratamentosunclassified